2021
DOI: 10.3389/fbioe.2021.759442
|View full text |Cite
|
Sign up to set email alerts
|

Comfort Evaluation of Slow-Recovery Ejection Seat Cushions Based on Sitting Pressure Distribution

Abstract: Sitting discomfort not only affects the health of pilots carrying out long-endurance missions but also affects operational performance. The experimental objects included four ejection seat cushions: N1 was a fast-recovery foam as the comparison group, and the experimental groups were slow-recovery foams with different indentation force deflection (IFD), named N2 (hard), N3 (mid), and N4 (soft). The sitting comfort of 20 participants was tested on the four cushions by using subjective rating and sitting pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Although the contact area was larger when the inclination angle increased, the fixed angle led to a non-uniform distributions of the force, where pressures were concentrated at the buttock and the shoulder areas. This might be the reason of the lowered comfort score in the 18-degree setting (Bao et al, 2021). Meanwhile, the position of the gravitational center was moved towards the posterior direction with the increases of the angles, this might restrict movement as well (Kim et al, 2014).…”
Section: Pressurementioning
confidence: 99%
“…Although the contact area was larger when the inclination angle increased, the fixed angle led to a non-uniform distributions of the force, where pressures were concentrated at the buttock and the shoulder areas. This might be the reason of the lowered comfort score in the 18-degree setting (Bao et al, 2021). Meanwhile, the position of the gravitational center was moved towards the posterior direction with the increases of the angles, this might restrict movement as well (Kim et al, 2014).…”
Section: Pressurementioning
confidence: 99%
“…It is difficult for users to evaluate the structure and parameters of a cushion, but easy to give clear feedback on the comfort of body parts [24,26]. Therefore, the subjective evaluation of BEC comfort was focused on the comfort rating of some key body parts, including buttocks, sciatic nodes, thighs, and thigh roots.…”
Section: Subjective Assessmentmentioning
confidence: 99%
“…Tang et al [23] used the sitting pressure distribution as an indicator to design the distribution of foams in the cushion, and found that the cushion with a bulging front had a more uniform pressure distribution. Bao et al [24] tested the sitting comfort of four cushions by using subjective rating and sitting pressure distribution analysis and showed that the slow-recovery cushions that were too soft or too hard would reduce the comfort. Carrigan et al [25] developed a cushion system based on the sensor air unit and showed that adjusting the pressure of inflating cushion units with pressure mapping could obtain a uniform pressure distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Akgunduz et al [ 15 ] found that the relationship between contact area, contact force, and peak pressure is also directly related to the anthropometry and the cushion’s ability to deform under the weight of the subject. In fact, the effect of human-chair contact pressure and deformation is closely related to the cushion hardness and material [ 16 , 17 ], but also to the sitting depth [ 18 ] and the footrest height. For aged care seating, armrests were essential for ease of entry and egress [ 19 ].…”
Section: Introductionmentioning
confidence: 99%